DEPRESSION, ANXIETY, STRESS IN THE THIRD TRIMESTER OF PREGNANCY AND THE RELATIONSHIP WITH HUSBAND/PARTNER (Vietnam Journal of Community Medicine, 2026)
Objectives: 1) To determine the prevalence of symptoms of depression, anxiety, and stress in pregnant women during the last trimester of pregnancy using the DASS-21 scale; 2) To investigate the association between the husband/partner relationship and depression, anxiety, stress in pregnant women during the third trimester of pregnancy.Subjects and Methods: This was a cross-sectional descriptive study on 232 pregnant women in their third trimester of pregnancy at Hue University of Medicine and Pharmacy Hospital and Hue Central Hospital from July 2024 to May 2025.Results: Anxiety symptoms were the most common manifestations, with a prevalence of 22,8%, while depression and stress were less frequent, with similar rates 6,5%. Relationship characteristics with a husband/partner associated with depression, anxiety, and stress in the third trimester of pregnant women (p
Keywords: Depression, anxiety, stress, pregnant women, third trimester.